The Transformation of Tech in Asia Indonesia into Subscription Based Digital Media amid The Covid-19 Pandemic - Deandra Syarizka (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The Covid-19 pandemic has accelerated digital adoption and increased the profitability of subscription business model of global digital media companies. Digital media companies in the United States have proven that the subscription business model can be a more stable source of income for journalism than advertising. The success story of digital media subscription in the United States has inspired Indonesian digital media to implement the subscription business model. This study aims to determine in which organizational growth phase the transformation of the Tech in Asia Indonesia business model is carried out, based on Greiner's growth theory. This study also attempts to analyze how the transformation of business model of Tech in Asia Indonesia affects the editorial team, and changes the way journalists work in producing news, based on Lueke's organizational change model. This qualitative research uses interviews, document studies and participant observation to collect primary data. The data is then processed and analyzed by data reduction techniques, data display and drawing conclusions. Researcher also use triangulation techniques for the validity of the data. The results of the study show that the transformation of business model of Tech in Asia Indonesia into a digital subscription model that happened amid the COVID-19 pandemic was carried out in the fifth growth phase within the organization. The transformation has also changed the structure of the editorial team to be more specialized, the production process through more editing stages, and to a more extensive communication culture within the organization. The selection of a soft paywall model for the Tech in Asia Indonesia subscription has proven to be a new revenue source that helps companies maintain their business to get through difficult times amidst the pandemic. This business model also expected to be a more stable source of income in the long term.